Characterization Of Canned Torbangun (Coleus Amboinicus Lour) Leaf Soup Quality And Its Total Migration Of Packaging Material - Endang Warsiki; Evy Damayanthy; Rizal Damanik (Department of Agroindustrial Technology, Bogor Agricultural University, 2009)
Torbangun soup is made by traditionally recipe as Batak cuisine. A packaging technique has applied by canned the soup to produce Torbangun soup for commercially market. An antioxidant is added to prevent rancidity and to prolong shelf life of canned soup. Regarding to quality analysis, the shelf life of canned Torbangun soup is 14 days in room temperature. The effort has been done by storage the product in cool temperature (5 - 8°C and 10 - 12°C) and resulted in longer shelf life until 22 days. In spite of antioxidant adding, pasteurization at temperature of 75°C for 15 minutes prior canned can result on longer shelf life of the soup. However, can is metal and it might some hazard substance migrate into product. The study showed that the amount of the total residue migrate from can into soup is lower than 10 mg/dm2 allowing by the Directive 90/128/EEC for aqueous food simulant. A total migration test using 95% alcohol gave a value of 37.4435 mg/dm2, means higher than that EU standard as 10 mg/dm2. Keyword: Torbangun leaf soup, total migration, canning method